2021
DOI: 10.1097/j.pain.0000000000002422
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of inhibitory and excitatory parvalbumin interneuron circuits in the dorsal horn

Abstract: Parvalbumin-expressing interneurons (PVINs) in the spinal dorsal horn are found primarily in laminae II inner and III. Inhibitory PVINs (iPVINs) play an important role in segregating innocuous tactile input from pain-processing circuits through presynaptic inhibition of myelinated low-threshold mechanoreceptors and postsynaptic inhibition of distinct spinal circuits. By comparison, relatively little is known of the role of excitatory PVINs (ePVINs) in sensory processing. Here we use neuroanatomical and optogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 88 publications
(205 reference statements)
1
26
0
Order By: Relevance
“…Our results indicate that these heterozygous PV cre ;tdTom mice were only able to capture 33.8 ± 2.2% of PV-immunoreactive (IR) neurons in the lumbar dorsal horn, yet they were highly specific (81.5 ± 2.3%) ( Figure S1D-E ). These proportions are similar to those reported in a recent study (Gradwell et al, 2022). Furthermore, our results indicate that in lamina IIi-III of the dorsal horn, 60.8 ± 2.8% of tdTom-positive neurons colocalized with PAX2 whereas only 42.61 ± 2.4% colocalized with Tlx3 ( Figure 1D-H ).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Our results indicate that these heterozygous PV cre ;tdTom mice were only able to capture 33.8 ± 2.2% of PV-immunoreactive (IR) neurons in the lumbar dorsal horn, yet they were highly specific (81.5 ± 2.3%) ( Figure S1D-E ). These proportions are similar to those reported in a recent study (Gradwell et al, 2022). Furthermore, our results indicate that in lamina IIi-III of the dorsal horn, 60.8 ± 2.8% of tdTom-positive neurons colocalized with PAX2 whereas only 42.61 ± 2.4% colocalized with Tlx3 ( Figure 1D-H ).…”
Section: Resultssupporting
confidence: 92%
“…Unlike in the cortex, where PV neurons are inhibitory, spinal PV neurons have been shown to be either excitatory or inhibitory, with the ratios ranging from 50 to 95% inhibitory (Hughes et al, 2012;Petitjean et al, 2015;Abraira et al, 2017;Gradwell et al, 2022). Using a multi-labelling fluorescence in situ hybridization approach on C57BL/6 male mice, we examined the neurochemical nature of the lamina IIi-III dorsal horn PV neurons.…”
Section: The Majority Of Dorsal Horn Pv Neurons Are Inhibitorymentioning
confidence: 99%
See 1 more Smart Citation
“…What progress have we made in our study of sensory processing and its modulation in the spinal cord since 1965? The opportunities provided by the selective optical activation or inhibition of particular primary afferents or of distinct CNS neuronal populations ( 20 24 ), combined with chemogenetic manipulations, particularly DREADDS, which enable the select activation or suppression of defined subsets of neurons ( 25 27 ) as well as targeted CRISPR gene editing ( 28 ), is a total game changer—at last we can identify the specific function of particular sets of neurons. Furthermore, our ability to dynamically capture the activity profiles of defined neuronal populations and establish their relationships to behavioral reactions that reflect pain in awake behaving mice is another profound technical breakthrough ( 29 , 30 ), as is the use of machine learning to capture the data, and artificial intelligence to process and model it ( 31 , 32 ).…”
Section: Introductionmentioning
confidence: 99%
“…Early efforts to classify excitatory and inhibitory neurons by their spiking pattern, morphology, and neurochemical phenotype (Grudt and Perl 2002;Prescott and De Koninck 2002;Ruscheweyh and Sandkühler 2002;Yasaka et al 2010) have been augmented more recently by molecular techniques to identify and manipulate genetically-defined neuron types (Hantman et al, 2004;Duan et al, 2014;Petitjean et al, 2015Petitjean et al, , 2019Abraira et al, 2017;Zhang et al, 2018;Peirs et al, 2020Peirs et al, , 2021. However, genetically-defined neuron types are often heterogeneous and extra steps must be taken to subdivide them into functionally homogeneous groups (Gradwell et al, 2021;Peirs et al, 2021). Decades of research have revealed SDH circuitry to be much more complex than envisioned by Melzack and Wall (for reviews see Peirs and Seal, 2016;Lechner, 2017).…”
Section: Introductionmentioning
confidence: 99%